Ethnicity and long-term vascular outcomes in Type 2 diabetes: A prospective observational study (UKPDS 83) - Davis, T; Coleman, R; Holman, R (2014)
Aims: Evidence of ethnic differences in vascular complications of diabetes has been inconsistent. The aim of this study was to examine the relationship between ethnicity and long-term outcome in a large sample of individuals with newly diagnosed Type 2 diabetes. Methods: In a prospective observational study of 4273 UK Prospective Diabetes Study participants followed for a median of 18 years, 3543 (83%) were White Caucasian, 312 (7%) Afro-Caribbean and 418 (10%) Asian Indian. Relative risks for predefined outcomes were assessed comparing Afro-Caribbean and Asian Indian with White Caucasian using accelerated failure time models, with adjustment for cardiovascular risk factors and other potentially confounding variables. Results: During follow-up, 2468 (58%) participants had any diabetes-related end point, 1037 (24%) a myocardial infarction and 401 (9%) a stroke, and 1782 (42%) died. Asian Indian were at greater risk (relative risk, 95% confidence interval) for any diabetes-related end point (1.18, 1.07-1.29), but at lower risk of all-cause mortality (0.89, 0.80-0.97) and peripheral vascular disease (0.43, 0.23-0.82), vs. White Caucasian. Afro-Caribbean participants were at lower risk for all-cause mortality (0.84, 0.76-0.93), diabetes-related death (0.75, 0.64-0.88), myocardial infarction (0.55, 0.43-0.71) and peripheral vascular disease (0.55, 0.33-0.93) vs. White Caucasian. No ethnicity-related associations were found for stroke or microangiopathy. Conclusions: Asian Indian ethnicity is associated with the greatest burden of disease, but not with an increased risk of major vascular complications or death. Afro-Caribbean ethnicity is associated with reduced risk of all-cause and diabetes-related death, myocardial infarction and peripheral vascular disease, suggesting an ethnicity-specific protective mechanism. © 2013 Diabetes UK.